The Impact of Online and Offline Learning on Social Development of Early Childhood in The Covid-19 Pandemic - Vina Ovionita; Saridewi Saridewi (Universitas Pendidikan Indonesia Kampus Serang, 2022)
In the Covid-19 pandemic, children's social skills are underdeveloped. It happens because the learning system requires children no longer to interact with peers. Thus, they tend to play alone by using a cellphone and not looking for friends to play with and learn together. For this reason, this study aimed to determine the impact of online and offline learning on the social development of early childhood during the Covid-19 pandemic at the Pembina Lengayang State Kindergarten. This type of research used descriptive quantitative methods. The sampling technique used was the cluster sampling technique, namely the area sampling technique for determining the sample if the area to be studied was very large. Data were collected using observation, interviews, and documentation and analyzed using descriptive statistics with the help of SPSS for window 23. Based on the frequency test results through SPSS 23, out of 15 children, 14 children were classified as not good (93.3%), and one child was classified as good (6.7%). Meanwhile, the offline learning results revealed that out of 15 children, 100% of children were in the classification of not good social development. Then, there was no significant difference between the children's social development results through online and offline learning in the significance test. From the t-test or hypothesis testing results, it was found that the value of sig 2-tailed on children's social development both online and offline was 0.05. It indicates that Ha1 and Ha2 were accepted. In other words, there was an impact of online and offline learning on the social development of children at the Pembina Lengayang State Kindergarten.